Efficiency of powered systems for interproximal enamel reduction (IER) and enamel roughness before and after polishing—an in vitro study - Zingler, Sebastian; Sommer, Andreas Berthold; Şen, Sinan; Saure, Daniel; Langer, Jochen; Guillon, Olivier; Lux, Christopher J. (Clinical oral investigations, 2016)
This aims to evaluate the efficiency of three different powered interproximal enamel reduction (IER) systems and to assess enamel roughness before and after polishing using different polishing times.
Gesehen am 06.05.2020
Published: 30 September 2015